2015
DOI: 10.2135/cropsci2015.04.0229
|View full text |Cite
|
Sign up to set email alerts
|

Response of Cultivated and Wild Barley Germplasm to Drought Stress at Different Developmental Stages

Abstract: Little is known about response of root‐related traits of barley (Hordeum vulgare L. subsp. vulgare; hereafter, Hvu) and its wild relative H. vulgare L. subsp. spontaneum (K. Koch) Thell. (hereafter, Hsp) to drought stress. Three separate experiments were conducted to assess these traits at germination, vegetative, and reproductive stages. Drought stress significantly reduced germination percentage and rate, primary root number, and shoot and root length of seedlings. Using pot experiment, drought stress reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…However, by all of these methods, most of the drought tolerant genotypes were from the WB group. Similar results have been reported in previous studies of root-related traits (Barati et al 2015), which most of genotypes with vigorous root system (higher root dry weight, depth and area) were from the wild barley accessions. In the other study on wild barley species, the genotypes from H. murinum and H. marinum had more yield stability on drought stressed environment compared to the cultivated one (Barati et al 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, by all of these methods, most of the drought tolerant genotypes were from the WB group. Similar results have been reported in previous studies of root-related traits (Barati et al 2015), which most of genotypes with vigorous root system (higher root dry weight, depth and area) were from the wild barley accessions. In the other study on wild barley species, the genotypes from H. murinum and H. marinum had more yield stability on drought stressed environment compared to the cultivated one (Barati et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a much fuller exploitation of these genetic resources by breeding for economically important agronomic traits is warranted. Barati et al (2015) also evaluated the root characteristics of a cultivated and WB germplasm, mostly originated from Iran, and identified genotypes with high drought tolerance at each developmental stage based on root-related traits. In a recent study, Barati et al (2018) evaluated agro-morphological and yield-related traits associated with drought tolerance in 80 barley genotypes belonging to 15 wild species and identified wild barley genotypes with favorable characteristics and high drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…For this, we focused primarily the root trait variation, to find major genetic players contributing to different root systems in barley and secondly to dissect the putative genetic interplay of root and shoot traits. It has been reported that the root architecture takes major role in plant adaptation to drought (Chloupek et al, 2010; Wasson et al, 2012; Barati et al, 2015). Although, numerous GWAS studies have been made on barley diversity analysis by Nandha and Singh (2014) and Russell et al (2014), but genetic dissection of root traits remained fragmented due to difficulty for its phenotypic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the significant effect of growth stage, soil water content, and soil layer on wheat root weight density in these experiments ( P < 0.01). Similarly, Barati et al (2015) revealed that the effect of drought stress on genotypes was highly dependent on developmental stage and the intensity of water limitations. Moreover, Guan et al (2015) investigated the root weight density of wheat at tillering, flowering and ripening, revealing a maximum value at flowering.…”
Section: Discussionmentioning
confidence: 99%